(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
This work proposes a critical reflection about the discursive construction of the Patagonia as an inter-subjective, relative, polysemic and historical distance. In the present analysis, we distinguish between different ideas of the region, such as territory, geocultural unit, imaginary geography, existential residence and locus of enunciation, and we indicate some of its overlapping and more frequent conceptual contradictions. We criticize the essentialist and folklorist perspectives of the region and its literature, as well as the inscription of the Patagonia in the national and nationalistic cultural cartographies.